A taxonomic revision of the nominotypical subgenus Tiphia Fabricius, 1775(Hymenoptera: Tiphiidae: Tiphiinae) from China, with three new species and a key to the Chinese species - Han, Qian; Wang, He-Sheng; Chen, Bin; Li, Ting-Jing (Zootaxa, 2023)
In this study, twenty-one species of the nominotypical subgenus Tiphia Fabricius from China are described and illustrated in detail, including three new species and ten new records as follows: Tiphia (Tiphia) flavobrunnea sp. nov., T. (T.) longistria sp. nov., T. (T.) mediocarinata sp. nov., T. (T.) aurata Allen, 1975, T. (T.) borneana Cameron, 1907, T. (T.) dayi Krombein, 1982, T. (T.) dutti Allen, 1975, T. (T.) incisa Cameron, 1897, T. (T.) lawrencei Allen, 1975, T. (T.) pulchaukiae Allen, 1975, T. (T.) s-secunda Allen, 1975, T. (T.) toreuta Boni Bartalucci, 2010 and T. (T.) weismani Krombein, 1982. In addition, the females of four species are firstly described, namely T. (T.) chihpenchia Tsuneki, 1986a, T. (T.) cilicincta Allen & Jaynes, 1930, T. (T.) mongolica Tsuneki, 1986b, and T. (T.) wuyiana Chen & Yang, 2003. And the males of four following species are also firstly described: T. (T.) choui Chen & Yang, 1991, T. (T.) nervidirecta Allen & Jaynes, 1930, T. (T.) pigmentata Allen & Jaynes 1930, and T. (T.) taiwana Ishikawa, 1967. Based on our collections and relevant references, a key to the Chinese species of the subgenus Tiphia is firstly compiled.